3D Cold‐Trap Environment Printing for Long‐Cycle Aqueous Zn‐Ion Batteries. Issue 9 (30th December 2022) - Lu, Hongyu; Hu, Jisong; Zhang, Yan; Zhang, Kaiqi; Yan, Xiaoying; Li, Heqi; Li, Jianzhu; Li, Yujie; Zhao, Jingxin; Xu, Bingang
Abstract: Zn powder (Zn‐P)‐based anodes are always regarded as ideal anode candidates for zinc ion batteries owing to their low cost and ease of processing. However, the intrinsic negative properties of Zn‐P‐based anodes such as easy corrosion and uncontrolled dendrite growth have limited their further applications. Herein, a novel 3D cold‐trap environment printing (3DCEP) technology is proposed to achieve the MXene and Zn‐P (3DCEP‐MXene/Zn‐P) anode with highly ordered arrangement. Benefitting from the unique inhibition mechanism of high lattice matching and physical confinement effects within the 3DCEP‐MXene/Zn‐P anode, it can effectively homogenize the Zn 2+ flux and alleviate the Zn deposition rate of the 3DCEP‐MXene/Zn‐P anode during Zn plating–stripping. Consequently, the 3DCEP‐MXene/Zn‐P anode exhibits a superior cycling lifespan of 1400 h with high coulombic efficiency of ≈9.2% in symmetric batteries. More encouragingly, paired with MXene and Co doped MnHCF cathode via 3D cold‐trap environment printing (3 DCEP‐MXene/Co‐MnHCF), the 3DCEP‐MXene/Zn‐P//3DCEP‐MXene/Co‐MnHCF full battery delivers high cyclic durability with the capacity retention of 95.7% after 1600 cycles. This study brings an inspired universal pathway to rapidly fabricate a reversible Zn anode with highly ordered arrangement in a cold environment for micro‐zinc storage systems. Abstract : An innovative 3D cold trap environment printing technology (3DCEP) is proposed in this work to fabricate a MXene/Zn‐P aerogel anode with highly aligned arrangement. Benefitting from unique high lattice matching and physical confinement effects inside the electrode, it can effectively inhibit the Zn dendrite growth and Zn‐P corrosion in electrolytes. Finally, a 3DCEP‐MXene/Zn‐P//MXene/Co‐MnHCF full cell with long cyclic life can be realized.